2015
DOI: 10.18055/finis6469
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of measured and simulated Mean Radiant Temperature. Case Study In Lisbon (Portugal)

Abstract: -Mean radiant temperature (Mrt) is one of the most relevant human bioclimatic indices, particularly suitable for assessing the influence of climatic parameters on thermal comfort outdoors. Mrt can be calculated either from physical measurements, carried out using a globe thermometer or a pyranometer and a pyrgeometer, in order to quantify short and long wave radiation fluxes, or through computer simulation. the first method, although accurate, entails the measurement of radiant fluxes from six directions, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The outdoor air temperature is shown in Figure 7a, and the simulated and measured indoor air temperatures are shown in Figure 7b, where the blue line indicates the measured indoor air temperature and the red dotted line represents the simulated indoor air temperature. The Pearson coefficient of the simulated and measured values is 0.969, which is close to that of 0.956 in a previous study [38]. Additionally, this research also calculated the RMSE and MAE of the simulated and measured data, whose values are 1.86 • C and 1.45 • C, respectively, which proves that Envi-met (5.5 version) is accurate enough to simulate the impacts of plants on the indoor air temperature.…”
Section: Simulation Toolsupporting
confidence: 87%
“…The outdoor air temperature is shown in Figure 7a, and the simulated and measured indoor air temperatures are shown in Figure 7b, where the blue line indicates the measured indoor air temperature and the red dotted line represents the simulated indoor air temperature. The Pearson coefficient of the simulated and measured values is 0.969, which is close to that of 0.956 in a previous study [38]. Additionally, this research also calculated the RMSE and MAE of the simulated and measured data, whose values are 1.86 • C and 1.45 • C, respectively, which proves that Envi-met (5.5 version) is accurate enough to simulate the impacts of plants on the indoor air temperature.…”
Section: Simulation Toolsupporting
confidence: 87%
“…Previous studies have shown that the model tool is very accurate for wind flow, urban microclimate pollutant dispersion, turbulence, and radiation fluxes simulation [25,26]. Moreover, the correlation coefficient between the simulated air temperature and the measured of the canyon street with Envi-met was 0.956, surpassing Solweig with the values of 0.866 and Rayman with the values of 0.867 [27]. Furthermore, The R 2 value between Envi-met simulated and experimental data indicates a strong correlation [28].…”
Section: Description Of the Simulation Toolmentioning
confidence: 93%
“…Compared with the other traditional computational fluid dynamic simulation software platforms, ENVI-met realizes the analysis of small scale changes in urban design, such as tree setting and building configuration [28,29], which makes it a widely used analytical tool in the field of the built environment. ENVI-met is also well known among the scientific community for its higher accuracy, with the Pearson value of its predictions being proved as 0.956, exceeding 0.866 (Solweig model) and 0.867 (Rayman model) [30,31]. The principles and mathematical models of ENVI-met can be seen in Bruse's paper [32].…”
Section: Evaluation Indexmentioning
confidence: 99%